2011
DOI: 10.5505/tjtes.2011.28009
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting morbidity in urgent repair of abdominal wall hernia with intestinal incarceration in adults

Abstract: AMAÇBu çalışmanın amacı erişkin hastalarda oluşan intestinal inkarserasyonlu karın duvarı fıtıklarında morbiditeyi etkileyen faktörleri araştırmaktır. GEREÇ VE YÖNTEMMart 1999-Mart 2008 tarihleri arasında 124 olgu (73 erkek) inkarsere intestinal fıtık tanısı ile acil ameliyat edildi. Olguların yaş ortalaması 61±13,87 idi. Ortanca fıtık süresi 5 yıl (0,1-30) bulundu. Fıtık tipi, fıtık süresi, yandaş hastalıklar, uygulanan cerrahi tedavi ve ameliyat sonrası komplikasyon bilgileri geriye dönük araştırıldı. BULGUL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Mortality, and morbidity are related to the development of bowel necrosis secondary to strangulation [8, 9]. In various studies performed, bowel resection has been reportedly required in 10-15% of the patients with strangulated abdominal wall hernias [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality, and morbidity are related to the development of bowel necrosis secondary to strangulation [8, 9]. In various studies performed, bowel resection has been reportedly required in 10-15% of the patients with strangulated abdominal wall hernias [2].…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, authors reported that advanced age, higher incidence rates of concomitant diseases and delayed referrals increased bowel resection and morbidity rates [10, 11]. In studies where patients aged ≤70 years with strangulated abdominal wall hernias were urgently operated, higher mortality rates were reported in the advanced age group [8, 11]. As indicated in various reports, in cases with strangulated abdominal wall hernias, most frequently hernial sac contains small bowel segments [1].…”
Section: Discussionmentioning
confidence: 99%
“…While mortality rates in IAAH are 1.4-13.4%, morbidity rates have been reported between 19-30%. Mortality and morbidity have been reported to be associated with strangulation and bowel resection (8,10) (10) reported morbidity rates as 11.4% and 20%, respectively, and mortality rates as 5.06% and 3%, respectively, in their study. In our study, the mortality rate was 4.8%, and the morbidity rate was 13.7%, consistent with the literature.…”
Section: Discussionmentioning
confidence: 82%
“…980089 indication, priority is given to the removal of necrotic tissues, rather than to the closure of the defect, whereas different techniques are used for elective operations by considering the status of patients (Vano-Galvan 2009) Before discussing these techniques, we find it useful to remind that such cases are the patients who are typically elderly and have comorbid diseases and high risk of postoperative complications (El Saadi 2005, Garavello 2004) . In Ezer et al's study conducted in 2011, a postoperative complication rate of 20% and a mortality rate of 3% were reported, which revealed a significant correlation between age and comorbid diseases and postoperative morbidity and mortality (Ezer 2011). Considering that the cases with giant inguinoscrotal hernia are the patients who are typically elderly and have comorbid diseases will provide better understanding of the importance of early diagnosis and early treatment in minimizing morbidity and mortality.…”
Section: Discussionmentioning
confidence: 98%